The sheep meat sector: strategies of actors in the steppe region of Tiaret in Algeria - Zemour H.; Sadoud M. (Pastoralism and sustainable development: proceedings, 2021)
The development of sheep farming has always been a priority for Algeria to meet the population's needs for animal proteins. The objective of this article is to examine beyond the sheep meat producers the functioning of the sector in the region of Tiaret. The morphology and geographical position of the latter give it an agro-pastoral character. Horse dealers (collectors, 22 respondents) and butchers (31 respondents) are considered to be the main players in the sheep meat marketing circuits in the region. They act as mediators between producers and consumers. This study has enabled us to observe that actors in the region are generally better informed about supply, demand and price levels thanks to an efficient information network and a permanent presence in the market. They are characterized by their practices which are particularly aimed at maximizing the margin, followed by transactions which consist in buying when prices are low and selling under advantageous conditions. The times of sale where the prices are higher are the religious periods of Aid El-adha (sacrifice) and Ramadhan.
International e-Workshop organized in the framework of PACTORES project, 2021/07/14-15, Valenzano, Bari, (Italy)